2010
DOI: 10.1007/s11101-010-9187-8
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene-based plant defenses

Abstract: Pentacyclic triterpenes are abundant in the plant kingdom and have a wide array of pharmacological activities. They also have insect antifeedant effects and therefore apparently play a role in plant defense. In this paper, we describe the insecticidal activity of pentacyclic triterpenes of plant origin from different chemical classes on several insect pests (Spodoptera littoralis, Leptinotarsa decemlineata and Myzus persicae), their phytotoxic properties and their selective cytotoxic effects on insect-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 93 publications
2
49
2
Order By: Relevance
“…There is a previous study in which its inactivity against M. persicae and S. littoralis is reported [40]. The divergence in the result on M. persicae found with the present work may be due to different aphid instars used in the tests.…”
Section: Resultscontrasting
confidence: 72%
“…There is a previous study in which its inactivity against M. persicae and S. littoralis is reported [40]. The divergence in the result on M. persicae found with the present work may be due to different aphid instars used in the tests.…”
Section: Resultscontrasting
confidence: 72%
“…In the current study, oleanolic acid (2) was active against the S. granarius, T. confusum and A. obtectus (Tables 3-6 and Figures S2-S4). In accordance with our results, it has been reported that oleanolic acid (3) have toxic effect against Spodoptera frugiperda JE Smith, Spodoptera littoralis, Leptinotersa decemlineata, Myzus persicae and Bemisia tuberculata [56,58,59]. On the other hand, Pungitore et al (2005) indicated that oleanolic acid (2) isolated from Junellia aspera exhibited less toxicity against Sitophilus oryzae (L.) [54].…”
Section: Insecticidal Properties Of the Extracts And Pure Olive Leaf supporting
confidence: 91%
“…However, there have been some reports on insecticidal properties of the leaf extracts and its pure metabolites against various insects species [53][54][55][56][57][58][59][60]. Zia et al (2011) tested the extract of olive leaves against chickpea beetle, Callosobruchus chinensis and they found it active against the beetle [57].…”
Section: Insecticidal Properties Of the Extracts And Pure Olive Leaf mentioning
confidence: 99%
“…34 The insectidal activity of a wide range of plant pentacyclic triterpenes from different chemical classes on several insect pests (Spodoptera littoralis, Leptinotarsa decemlineata and Myzus persicae) has been recently reviewed. 471 The presence of different substituents at C-3 and C-28 modulate these insecticidal effects.…”
Section: Triterpenesmentioning
confidence: 99%